Primary Aldosteronism Associated with Multiple Adrenocortical Micronodules in a Patient with Renal Cell Carcinoma. (24th February 2020) - Oba, Kazuhito; Chiba, Yuko; Matsuda, Yoko; Kumakawa, Takeshi; Aoyama, Rie; Akahoshi, Miho; Hashimoto, Seiji; Tachibana, Aya; Toyoshima, Koichi; Kodera, Remi; Toyoshima, Kenji; Tamura, Yoshiaki; et al.
Abstract : A 47-year-old woman with a history of diabetes mellitus (DM) and obesity was admitted to our hospital for glucose control. She was detected to have hypertension (HT) and diagnosed with primary aldosteronism (PA) based on the high level of aldosterone to renin ratio and the results of the upright furosemide-loading test according to the criteria of the Japanese Society of Hypertension (JSH) guidelines. Computed tomography revealed left renal tumor and adrenocortical adenoma. She underwent left nephrectomy and adrenalectomy. The pathological findings were clear-cell renal cell carcinoma (RCC) and nonfunctional adrenocortical adenoma. Her nonneoplastic adrenal tissue histologically revealed CYP11B2-positive multiple adrenocortical micronodules (MNs) and concomitant paradoxical hyperplasia of the zona glomerulosa. Therefore, MNs were thought to be responsible for PA in this patient. After surgery, HT was improved, and the result of upright furosemide-loading test after 12 months of surgery did not fulfill the criteria of PA according to the JSH guidelines. However, the adrenocorticotrophic hormone stimulation test was positive; considering the possibility of slight aldosterone overproduction from the right adrenal gland, the administration of spironolactone was started. Herein, we report a rare case of RCC in conjunction with PA histologically associated with MNs.